TINDAK PIDANA KORPORASI DAN UPAYA PENANGGULANGANNYA - Kusumo, Bambang Ali (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2005)
Abstract Lost caused by corporate crime on individual, society and state was very numerous, however, it is not easy to give penal sanction to such corporate. This is because, one other thing, there is many impediment in determining the responsibility and should of the corporate. Therefore, the effort to deterrent corporate crime not only relies on penal act, but also on non penal act infrastructure, so that integration of both will lessen the corporate crime. Keywords: requirement of customer, doing an injustice corporation, criminal law, lost